2019
DOI: 10.1097/corr.0000000000000946
|View full text |Cite
|
Sign up to set email alerts
|

Do External Supports Improve Dynamic Balance in Patients with Chronic Ankle Instability? A Network Meta-analysis

Abstract: Background To improve ankle stability in patients who have experienced an ankle sprain with residual symptoms of instability and/or objective joint laxity, external supports (such as taping, bracing, and orthotic insoles) are used sometimes. However, available randomized trials have disagreed on whether restraints improve balance in those individuals. In this situation, a network meta-analysis can help because it allows for comparing multiple treatments simultaneously, taking advantage not only of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In a systematic review and network meta-analysis (21 trials, n = 469), Tsikopoulos and colleagues 437 identified moderate evidence that external support of any type, including insoles plus bracing, bracing, insoles, and taping, was no more effective than controls in providing clinical benefit for postural stability and balance performance.…”
mentioning
confidence: 99%
“…In a systematic review and network meta-analysis (21 trials, n = 469), Tsikopoulos and colleagues 437 identified moderate evidence that external support of any type, including insoles plus bracing, bracing, insoles, and taping, was no more effective than controls in providing clinical benefit for postural stability and balance performance.…”
mentioning
confidence: 99%
“…However, a meta-analysis showed no positive effects of taping on proprioception in functional ankle instability despite the limitation of differences in participants studied, the type of taping used, the way in which the tape was applied, and the way proprioception was measured [ 12 ]. More recently, Tsikopoulos et al [ 19 ] found no significant effects of any tape on dynamic balance in patients with chronic ankle instability based on the Star Excursion Balance Test only. Based on the above lines of evidence, it was plausible that the protective effect of tape for preventing ankle reinjury was not likely to be due to enhanced proprioception.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the above lines of evidence, it was plausible that the protective effect of tape for preventing ankle reinjury was not likely to be due to enhanced proprioception. There are several techniques of ankle joint taping [ 12 , 19 ]. The taping method we used in this study had been frequently used clinically [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delahunt et al (2010) demonstrated that ankle joint taping was not able to positively influence dynamic postural stability in subjects with CAI. A recent meta-analysis (Tsikopoulos et al, 2019) also demonstrated that taping was not effective in improving dynamic postural control in patients with CAI. Conversely, some research (Andreo et al, 2018;Jelinek et al, 2019) concluded that KT and AT contributed to the balancing action during Y balance test.…”
Section: Effect Of Kt On Postural Control With Caimentioning
confidence: 99%